Why is Huawei's ownership so strange? A case study of the Chinese corporate and socio-political ecosystem. Issue 1 (2nd January 2021) - Hawes, Colin
ABSTRACT: One of China's best-known and most successful corporations is Huawei Technologies. Many view Huawei with suspicion, alleging that its opaque structure conceals ties with the Chinese government and Communist Party. However, Huawei claims to be a private corporation controlled by its employees and operating in a purely commercial way. This paper demonstrates how Huawei's strange ownership structure evolved via a series of adaptive survival mechanisms within a state-dominated political and corporate ecosystem. These included profit sharing joint ventures with state-owned enterprises and officials, co-opting a Communist Party branch within the firm, and doing an end run around the PRC Company Law with 'virtual' employee shares. Placing Huawei within this Chinese ecosystem challenges simplistic accounts of top-down government or Party control over the firm. Yet the compromises that ensured Huawei's growth and protection from predation have become maladaptive within the global political ecosystem, where China is increasingly viewed as a threat.